(untitled) (Bangladesh Journal of Public Administration, 2019)
The Cabinet Division of the Government of the Peoples‟ Republic of Bangladesh formed the Upazila Management Committee (UMC) on Social Security on 27 August 2018 to manage the overall coordination; monitoring and evaluation; database management; and beneficiary selection of all the social-security programmes being implemented at various government agencies in an Upazila. As per the administrative records, there were no documents available to prove that any UMC meeting held in the country and thereby it seemed to be not being functional since its establishment. Therefore, this baseline research was conducted to (a) assess the level of functionality of the UMC; (b) identify the causes; (c) find out suggestions to overcome the challenges. It was found that out of 64 upazilas, randomly selected one from each district, only 2 UMC meetings were held, and only 7 Upazila Nirbahi Officers had knowledge about the notification of the UMC. Since its establishment, the UMC of the Brahmanbaria Sadar has not been effective and functional. The reasons being (a) noncommunication of the notification with the UMC members through the formal procedure and (b) prominence of the activities related to the National Parliament Election. Therefore, the following recommendations have been made – (a) direct and formal communication of the notification of the UMC with the members especially with the chairperson and the member-secretary; (b) training and awareness building for the UMC members; (c) rigorous monitoring by the Department of Social Services and (d) District Management Committee and the Divisional Management Committee should also be made functional immediately